Interstitial Mycosis Fungoides With Lichen Sclerosus-Like Clinical and Histopathological Features - (:unkn) unknown (LIPPINCOTT WILLIAMS & WILKINS, 2016)
Mycosis fungoides (MF) simulates a variety of dermatologic disorders histopathologically and clinically, well deserving the designation of a great mimicker. Interstitial MF is a rare, but well-recognized histopathological variant resembling the interstitial form of granuloma annulare or the inflammatory phase of morphea. From a clinical standpoint, MF can have a wide array of manifestations, including an anecdotal presentation with lesions clinically suggestive of lichen sclerosus (LS). We herein report a 25-year-old man with a history of patch-stage MF who later developed widespread LS-like lesions histopathologically consistent with interstitial MF. In some biopsies, additional features resembling LS were discerned. We think that our case might represent a unique variant of interstitial MF presenting with LS-like lesions. The diagnostic challenge arising from this uncommon presentation is discussed together with review of the literature.
Keywords: interstitial mycosis fungoides; lichen sclerosus; T-CELL; CUTANEOUS LYMPHOMAS; GRANULOMA-ANNULARE; ET-ATROPHICUS; DIAGNOSIS; LESIONS